SIFAT FISIK, KIMIA DAN AKTIVITAS ANTIOKSIDAN ABON DAGING AYAM DI KOTA PALU - Sukisman Sukisman; Abdul Halid; Abdul Rahim (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
One product well-known to be liked by people young and old is chicken meat floss, even though its quality is often overlooked by either the producer or consumer.  The aim of this research was to identify physical, chemical and anti-oxidant characteristics of chicken meat floss produced by micro – small – medium enterprises (MSME) in Palu city.  The research use a completely randomized design with eight samples utilized and replicated three times, therefore, there were 24 research samples.  Parameter analyzed included water content, protein, fat, ash, total microbes, and anti-oxidant activities.  The research results showed that the chicken meat floss producing and distributing in Palu city had water content ranging from 4.32% – 12.35%, ash content ranging from 4.20% – 5.91%, protein content ranging from 29.71% – 40.72%, fat content ranging from 17.74% – 21.98%, the number of total microbes ranging from 1.10 – 8.87 log cfu/g, and anti-oxidant activities as shown by Inhibition Concentration/IC50 ranging from 5126.42 ppm – 12674.90 ppm and the percentage of inhibition ranging from 20.89% – 51.16%.  The percentage of free radical inhibition of the chicken floss UMKM in Palu was varied, however, the UMKM with the highest effect of inhibition belong to UMKM 5 as shown by its low IC50 concentration (5126.42 ppm) and highest percentage of microbe inhibition (51.16%).